The doctor-patient relationship, bioethical considerations - Mendoza F., Alfonso (2018)
Despite the vertiginous changes in the professional medical practice due to the development of medicine in the contemporary world, the patient-doctor relationship continues being a cornerstone of the medical act. The objective of this paper is though that this relationship requires to be examined under a new vision, not only in light of what has been said above, but also because of the relaunching of the ethical reflection that the doctor-patient relationship is first of all an interpersonal encounter in which both sides deliberate together to take the right decision, always within the scope of the principles of bioethics and the fundamental rights of the human person.